2021
DOI: 10.1055/s-0041-1741001
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Curve of Reaching the Planned Limb Alignment in Robotic-Arm-Assisted Total Knee Arthroplasty

Abstract: Evidence on the learning curve associated with robotic-arm-assisted total knee arthroplasty (ra-TKA) is scarce and mostly based on operative time. Thus, the objective of this study was to assess a surgeon's learning experience based on accuracy to reach planned limb alignment and its impact on surgical-characteristics, limb-alignment, and perioperative-outcomes. A retrospective chart review was conducted on a consecutive series of 204 primary ra-TKAs (patients), performed by a single surgeon in a single instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…21 Pannu et al demonstrated 110 cases are needed to finally achieve the planned limb alignment when MAKO RAS system is utilized, seemingly aMA, although not explicitly described in the study. 22 In the present study, 20 initial cases were excluded due to the initial learning curve, but the results observed match previous learning curve studies demonstrating little to no learning curve in terms of implant position. 13,23,24 Winnock de Grave et al demonstrated superior outcomes of inverse kinematic when compared with aMA.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…21 Pannu et al demonstrated 110 cases are needed to finally achieve the planned limb alignment when MAKO RAS system is utilized, seemingly aMA, although not explicitly described in the study. 22 In the present study, 20 initial cases were excluded due to the initial learning curve, but the results observed match previous learning curve studies demonstrating little to no learning curve in terms of implant position. 13,23,24 Winnock de Grave et al demonstrated superior outcomes of inverse kinematic when compared with aMA.…”
Section: Discussionsupporting
confidence: 77%
“…A recent meta-analysis demonstrated better accuracy and better patient-reported outcomes with the use of RAS, not controlling for alignment, rather the planned and achieved alignment 21 . Pannu et al demonstrated 110 cases are needed to finally achieve the planned limb alignment when MAKO RAS system is utilized, seemingly aMA, although not explicitly described in the study 22 . In the present study, 20 initial cases were excluded due to the initial learning curve, but the results observed match previous learning curve studies demonstrating little to no learning curve in terms of implant position 13,23,24 .…”
Section: Accepted Manuscriptmentioning
confidence: 92%